Efektivitas “Metode Tebak Kata “ Untuk Meningkatkan Penguasaan Mufrodat Dalam Pembelajaran Bahasa Arab - Dede Rizal Munir; Siti Nurlatifah (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The problem in this research is the lack of students in mastering the Arabic Language Mufrodat MA YPPA CIPULUS Purwakarta West Java. The purpose of this research is to determine the effectiveness of abilities in mastering Arabic mufrodat through the application of the word guessing learning method in class in class . This research approach is a quantitative approach with the type of research being Classroom Action Research. The focus of this research is process and outcome focus. The research was carried out at MA YPPA CIPULUS Purwakarta Regency with research subjects being teachers and students of class X. Data was obtained through test, observation and documentation techniques. The conclusion of this research is that applying the word guessing method can improve students' ability to master Arabic mufrodat.